Molecular Aspects of Regional Pain Syndrome. (11th April 2020) - Baronio, Manuela; Sadia, Hajra; Paolacci, Stefano; Prestamburgo, Domenico; Miotti, Danilo; Guardamagna, Vittorio A.; Natalini, Giuseppe; Sullivan, Stephanie G. B.; Bertelli, Matteo
Abstract : The purpose of this review is to summarize the pathophysiology of complex regional pain syndrome (CRPS), the underlying molecular mechanisms, and potential treatment options for its management. CRPS is a multifactorial pain condition. CRPS is characterized by prolonged or excessive pain and changes in skin color and temperature, and/or swelling in the affected area, and is generally caused by stimuli that lead to tissue damage. An inflammatory response involving various cytokines and autoantibodies is generated in response to acute trauma/stress. Chronic phase pathophysiology is more complex, involving the central and peripheral nervous systems. Various genetic factors involved in the chronicity of pain have been identified in CRPS patients. As with other diseases of complex pathology, CRPS is difficult to treat and no single treatment regimen is the same for two patients. Stimulation of the vagus nerve is a promising technique being tested for different gastrointestinal and inflammatory diseases. CRPS is more frequent in individuals of 61–70 years of age with a female to male ratio of 3 : 1. Menopause, migraine, osteoporosis, and asthma all represent risk factors for CRPS and in smokers the prognosis appears to be more severe. The pathophysiological mechanisms underlying CRPS involve both inflammatory and neurological pathways. Understanding the molecular basis of CRPS is important for its diagnosis, management, and treatment. For instance, vagal nerve stimulation might have the potential for treating CRPS through the cholinergic anti-inflammatory pathway.